New Perspectives on Virtual and Augmented Reality - Finding New Ways to Teach in a Transformed Learning Environment, Chapter 18 - ViMeLa: Interactive Educational Environment for Mechatronics Lab in Virtual Reality - Toomas Tikk, Rain Eric Haamer, Dorota Kamińska, Anna Firych-Nowacka, Slawomir Wiak, Najmeh Rezaei, Marcin Lefik, Grzegorz Zwoliński, Tomasz Sapiński, Goga Cvetkovski, Lidija Petkovska, Paolo Di Barba, Maria Evelina Mognaschi, Mihail Digalovski, Maja Celeska and Gholamreza Anbarjafari (Routledge, 2020)
In this chapter, a blended-learning method using theory classes and virtual reality (VR) as an experimentation tool is presented. The work has been developed as a joint European project, ViMeLa. The main objective is to create a virtual Mechatronic laboratory for learning and teaching students in Mechatronics. In the frame of the project, flexible solutions are developed. For demonstration purposes, three use-cases have been developed: design, construction and operating principles of electric motors; industrial automation solution for controlling the process of sorting packages in a warehouse; and industrial and domestic waste sorting line with belt.
Keywords: ViMeLa project, virtual reality, construction of electrical machines, operating principles of electrical machines, sorting packages, sorting line